Volatile compound profiles and cytotoxicity in essential oils from rhizome of Curcuma aeruginosa and Curcuma zanthorrhiza - RIZKI FITRIA; DJAROT SASONGKO HAMI SENO; BAMBANG PONTJO PRIOSOERYANTO; HARTANTI; Waras Nurcholis (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Fitria R, Seno DSH, Priosoeryanto BP, Hartanti, Nurcholis W. 2019. Volatile compound profiles and cytotoxicity in essential oils from rhizome of Curcuma aeruginosa and Curcuma zanthorrhiza. Biodiversitas 20: 2943-2948. Cancer becomes one of the uncontagious diseases that occupy the top position in the cause of human death under 70 years in the world. Breast cancer is the most widely experienced cancer by women. The aim of this study was to obtain cytotoxic activity essential oil of Curcuma aeruginosa and Curcuma zanthorrhiza as antiproliferative substance of cancer cells and to analyze volatile profile of C. aeruginosa and C. zanthorrhiza essential oils. The essential oils were obtained from rhizomes of C. aeruginosa and C. zanthorrhiza by using hydrodistillation method. Volatile compositions of essential oils were analyzed using gas chromatography and mass spectrophotometry (GC/MS). The cytotoxic activities of the essential oil samples were evaluated using brine shrimp lethality test and against MCF-7 (Michigan Cancer Foundation-7) and Vero cells. The essential oils of C. aeruginosa, and C. zanthorrhiza showed cytotoxic activities to brine shrimp and MCF-7. Cytotoxic activity presented in essential oil from C. aeruginosa and C. zanthorrhiza showed lower activity compared with Doxorubicin. The major compounds of C. aeruginosa were tropolone (18.1%), eucalyptol (17.9%), and curcumol (5.7%), whereas C. zanthorrhiza were xanthorrhizol (26.8%), b-curcumene (17.0%), ar-curcumene (15.0%), and germacrone (5.4%).